ALTERNATIVAS DE DESTINAÇÃO DOS RESÍDUOS SÓLIDOS DA COMUNIDADE AGROVILA RIBEIRO NOVO COMO FORMA DE PLANEJAMENTO AMBIENTAL - ALAGOINHA/PB (REMUNOM, 2025)
The management of solid waste is a pressing concern in contemporary discourse, with varying degrees of success in different countries. In some nations, waste disposal is conducted responsibly, whereas in others, it is discarded in an environmentally harmful manner, compromising public health and well-being. This monographic research investigates the solid waste management practices in Agrovila Ribeiro Novo, a community located in the municipality of Alagoinha, Paraíba state, Brazil. Initially, solid waste was deposited in an open area, but following community demands, the local government initiated weekly waste collection, transporting the waste to the old Alagoinha landfill. Subsequently, with the construction of the Guarabira sanitary landfill, the waste was redirected to this new facility. This study aims to examine the solid waste management issues in the community, assess the resident’s contribution to environmental preservation, and propose environmental planning strategies for this locality.